UTILIZATION OF TOFU LIQUID WASTE INTO BIOGAS: REVIEW - Lukhi Mulia Shitophyta; Sarifa Kaisupy; Indah Puspita Sari (Universitas Lambung Mangkurat, 2021)
Tofu production produces by-products in the form of liquid waste and solid waste. Tofu liquid waste which contains organic compounds has not been able to be managed properly. Industry owners only disposed of wastes into the environment. It causes water pollution and unpleasant odors around the tofu industry. One of the solutions to reduce environmental pollution is to utilize tofu liquid waste as alternative energy, namely biogas. The management of tofu liquid waste into biogas for the household scale tofu industry can use a fixed bed reactor, batch scale anaerobic reactor, and anaerobic sludge blanket (UASB) up-flow reactor. The UASB reactor is the best reactor for processing tofu liquid waste into biogas on a household scale. The volume of biogas produced by the UASB reactor was 11.115 liters, while the volume of biogas produced by the fixed bed reactor and batch scale anaerobic digester reactor was 3.5 liters and 1.525 liters, respectively.